2022
DOI: 10.1249/jes.0000000000000282
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia Related to Human Immunodeficiency Virus: Protective Effects of Exercise

Abstract: Sarcopenia is increasingly common among people with HIV, and combined exercise at higher intensity is a strategy to prevent its development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…A recent meta-analysis carried out by our study group showed that sarcopenia is highly prevalent (24.1%) in PLWH, who were 6.1 times more likely to develop sarcopenia than people without HIV 21 . In addition to aging, sarcopenia among PLWH is caused by different factors linked to HIV management, such as mitochondrial dysfunction, persistent inflammation, and formation of reactive oxygen species 20 , in a phenomenon called “premature” or “accelerated” aging 32 . Some behavioral and lifestyle factors also play a role, where PLWH present a high prevalence of physical inactivity, smoking, and food insecurity 20 , 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis carried out by our study group showed that sarcopenia is highly prevalent (24.1%) in PLWH, who were 6.1 times more likely to develop sarcopenia than people without HIV 21 . In addition to aging, sarcopenia among PLWH is caused by different factors linked to HIV management, such as mitochondrial dysfunction, persistent inflammation, and formation of reactive oxygen species 20 , in a phenomenon called “premature” or “accelerated” aging 32 . Some behavioral and lifestyle factors also play a role, where PLWH present a high prevalence of physical inactivity, smoking, and food insecurity 20 , 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to aging, sarcopenia among PLWH is caused by different factors linked to HIV management, such as mitochondrial dysfunction, persistent inflammation, and formation of reactive oxygen species 20 , in a phenomenon called “premature” or “accelerated” aging 32 . Some behavioral and lifestyle factors also play a role, where PLWH present a high prevalence of physical inactivity, smoking, and food insecurity 20 , 33 , 34 . Although under investigated, we believe that sarcopenia is an emerging health-related condition affecting PLWH, which will face the burden of aging-related sarcopenia and HIV management in the years to come.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, not unexpectedly, participants with sarcopenia in these two categories in our study had the most correlation with parameters associated with worse physical health‐related QOL. In other words, these two definitions were able to identify individuals with the highest risk of poor health outcomes, and evidence‐based interventions for sarcopenia to prevent future disability are urgently required for these individuals [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…22) In fact, it has been suggested that inflammation measured by circulating levels of IL-6 is the only known cross-sectional and longitudinal predictor of multimorbidity and one of the strongest predictors of incident mobility loss and disability in activities of daily living. 23) It is of interest to note that some authors have argued recently that similar mechanisms are active in patients with human immunodeficiency virus 24) or COVID-19 25) because both exhibit a sarcopenic phenotype.…”
Section: The Principal Clinical Manifestations Of Sarcopeniamentioning
confidence: 99%